Variable- and fixed-structure augmented interacting multiple-model algorithms for manoeuvring ship tracking based on new ship models - Semerdjiev, Emil; Mihaylova, Ludmila (Zielona Góra: Uniwersytet Zielonogórski)
Real-world tracking applications are related to a number of difficulties caused by the presence of different kinds of uncertainty, e.g. unknown or incompletely known system models and statistics of random processes or abrupt changes in the system modes of functioning. These problems are especially complicated in the marine navigation practice, where the commonly-used simple models of rectilinear or curvilinear target motions are not adequate for highly non-linear dynamics of the manoeuvring ship motion.
Keywords: nteracting Multiple Model (IMM) algorithm; model uncertainty; state and parameter estimation